2018
DOI: 10.1155/2018/4365739
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of Scutellariae Barbatae Herba for Treating Hepatocellular Carcinoma Based on Network Pharmacology

Abstract: As the fifth most common type of malignant cancers globally, hepatocellular carcinoma (HCC) is the second leading cause of cancer-related mortality worldwide. As a long-time medicinal herb in Traditional Chinese Medicine (TCM), Scutellariae Barbatae Herba (SBH) has also been used for treating various cancers including HCC, but its underlying mechanisms have not been completely clarified. Presently, an innovative network-pharmacology platform was introduced to systematically elucidate the pharmacological mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…In recent years, network pharmacology analysis was successfully used to predict the underlying function mechanisms of TCM formulas for cancer, depression, and cardiovascular disease treatment (Zhao et al, 2019). Network pharmacology is a systems biology-based methodology for evaluating pharmacokinetics (ADME properties of drugs) and target prediction, as well as investigating the multipharmacological effects of traditional medicines at the molecular level (Di et al, 2018;Gong et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, network pharmacology analysis was successfully used to predict the underlying function mechanisms of TCM formulas for cancer, depression, and cardiovascular disease treatment (Zhao et al, 2019). Network pharmacology is a systems biology-based methodology for evaluating pharmacokinetics (ADME properties of drugs) and target prediction, as well as investigating the multipharmacological effects of traditional medicines at the molecular level (Di et al, 2018;Gong et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Pathway and network analysis and protein-protein interactions are common methods for NP [68, 23]. Oral bioavailability [24] is an essential parameter for drug absorption and utilization; therefore, NP studies commonly use this alone or in combination with other parameters, including drug likeness, Caco-2 permeability, and drug half-life, as filters to select compounds from herbs [6, 7, 25]. Other methods, such as molecular docking, are also used in many NP studies [6, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Bing et al [6] used NP methods to indicate that licochalcone a and beta-sitosterol in Fuzhengkangai were active compounds to overcome drug resistance. Gong et al [25] found that TTR might be a potential treating target of hepatocellular carcinoma by using NP methods. Therefore, we can conclude that current NP research mainly focused on NP methods (including experimental validation) and using them to explore the molecular mechanisms of TCM for some critical diseases such as cardiovascular diseases and cancers.…”
Section: Discussionmentioning
confidence: 99%
“…TCMSP is a unique system pharmacology database of Chinese herbal medicines with data on absorption, distribution, metabolism, and excretion (ADME)-related parameters of herbal ingredients as well as the relationships between diseases, targets, ingredients, and drugs [ 18 ]. The active compounds of HGWD were primarily screened based on oral bioavailability (OB) and drug-like (DL) properties, the two important indicators for bioinformatics evaluation of ADME characteristics [ 19 ]. The OB is a major pharmacokinetic parameter of oral drugs and is the proportion of oral drug dose in the systemic circulation [ 20 ].…”
Section: Methodsmentioning
confidence: 99%